Clinical and Cerebrospinal Fluid Predictors of Sensorineural Hearing Loss in Adults with Acute Bacterial Meningitis: A Systematic Review and Meta-Analysis - I Gusti Agung Ayu Gita Lavenia Shanty; Anak Agung Raka Sudewi; Ni Made Susilawathi (Sriwijaya Journal of Neurology, 2026)
Background: Sensorineural hearing loss (SNHL) is the most frequent neurological sequela of acute bacterial meningitis (ABM) in adults, yet its admission-available clinical and cerebrospinal fluid (CSF) determinants have not been synthesised for adults specifically. Objective: To pool the prevalence and predictors of hearing loss after adult ABM and to quantify its variation by causative pathogen. Methods: PubMed, Scopus and Web of Science were searched for cohort studies and randomized trials reporting hearing loss in adults with ABM. Eleven studies were eligible; six non-overlapping cohorts (1,640 adults assessed for hearing) were pooled using a DerSimonian–Laird random-effects model on logit-transformed proportions, with pathogen subgroups and sensitivity analyses. Pooled proportions and odds ratios were used for this dichotomous outcome. Results: The pooled prevalence of hearing loss was 35.2% (95% CI 19.0–55.7; I²=98.0%; prediction interval 2.4–92.4%), with a marked pathogen gradient: Streptococcus suis 66.4%, mixed ABM 42.2%, Streptococcus pneumoniae 36.3% and Neisseria meningitidis 6.6%. Hearing-loss-specific predictors included advanced age (OR 3.65), otitis media (OR 2.58) and a virulent epf strain (OR 3.42), while serotype 23F was protective (OR 0.36); low CSF glucose and high CSF protein were associated with hearing loss. Adjunctive dexamethasone was associated with lower odds (OR 0.43; 95% CI 0.29–0.65). Conclusion: About one in three adult ABM survivors develops hearing loss, peaking in S. suis meningitis. Older age, otitis, virulent pathogens and severe CSF derangement mark high risk, and early dexamethasone appears protective, supporting structured audiological surveillance.